PREDICTION OF SULFAMETHOXAZOLE AND TRIMETHOPRIM PLASMA LEVELS FROM TABLETS AND DISSOLUTION MEDIA OF PHYSIOLOGICAL RELEVANCE - RIOS-RODRIGUEZ, JOSE MANUEL; REYES-RAMIREZ, FELIPE DINO; RUIZ-SEGURA, JUAN CARLOS; MEDINA-LOPEZ, JOSE RAUL (International Journal of Applied Pharmaceutics, 2024)
Objective: To estimate plasma concentrations-time profiles of Sulfamethoxazole (SMZ) and Trimethoprim (TMP) from fixed-dose combination formulations through in vitro data of dissolution media of physiological relevance and a convolution model. Methods: Dissolution profiles of SMZ/TMP tablets (400/80 mg) were obtained with USP paddle apparatus at 100 rpm and 900 ml of 0.1 N HCl, pH 4.5 acetate buffer, and pH 6.8 phosphate buffer. The reference drug product and two generic formulations were tested. Drugs were quantified by a derivative method. Dissolution profiles were compared with model-dependent and independent methods. SMZ/TMP plasma levels were simulated with dissolution data and published in vivo information. Percent of prediction error (PE) for peak plasma concentration (Cmax) and area under the curve from zero time to infinity (AUC0-inf) at each condition were calculated. Results: In all used conditions, similar dissolution profiles were found excepting for TMP at pH 1.2 (f2<50). The in vitro release performance for reference and generic formulations was explained by the Weibull function only for SMZ at pH 6.8 and TMP at pH 4.5. Values of PE>19% for both generic formulations were found with TMP at pH 1.2. Conclusion: Significant differences in TMP dissolution profiles of generic formulations at pH 1.2 reflect the subsequent differences found in predicted Cmax and AUC0-inf.